2013
DOI: 10.1159/000347124
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CREB in Primary Pterygium and Correlation with Cyclin D1, ki-67, MMP7, p53, p63, Survivin and Vimentin

Abstract: Aim: Ultraviolet (UV) B irradiation induces gene expression that leads to skin cancer. Among the transcription factors induced by UVB radiation exposure, the cyclic AMP response element-binding protein (CREB) is significant. Since several factors downstream of CREB signaling are known to be involved in pterygium pathogenesis, we investigated CREB expression in pterygial and human conjunctival tissues to evaluate if a similar expression pattern is present. Moreover, we analyzed the correlation with CREB express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Previous studies have indicated that pterygium is associated with numerous risk factors, including ultraviolet (UV) radiation (2)(3)(4)(5), viral infection (6)(7)(8), hereditary factors (9)(10)(11), immunological factors (12), aseptic inflammation (13), environmental irritation from wind, dust or trauma, smoke and ocular dryness (14). Recently, increased levels of the transcription factors cAMP response element-binding protein (15), cytochrome P450 1A1 protein (16), phospholipase D (17), and aquaporin-1 and -3 (18) have been implicated as risk factors for pterygia development. UV radiation remains a well-established pathogenic factor of pterygium based on epidemiological evidence (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that pterygium is associated with numerous risk factors, including ultraviolet (UV) radiation (2)(3)(4)(5), viral infection (6)(7)(8), hereditary factors (9)(10)(11), immunological factors (12), aseptic inflammation (13), environmental irritation from wind, dust or trauma, smoke and ocular dryness (14). Recently, increased levels of the transcription factors cAMP response element-binding protein (15), cytochrome P450 1A1 protein (16), phospholipase D (17), and aquaporin-1 and -3 (18) have been implicated as risk factors for pterygia development. UV radiation remains a well-established pathogenic factor of pterygium based on epidemiological evidence (19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…The tumor-like characteristics of pterygium are expressed when reproliferation occurs after excisional surgery. 9 , 10 Although various surgical procedures, including adjunctive treatments, have been proposed for the treatment of pterygium, recurrence remains a significant problem after surgical excision. 11 13 …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Because of these characteristics, pterygium was previously considered a degenerative disorder. However, recent studies have proven that pterygium also has proliferative histological characteristics, [4][5][6][7][8][9] such as mild dysplasia, local invasiveness, and abnormal p53 gene expression, and clinical features, including a high recurrence rate following pterygium excision.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have proven that pterygium also has proliferative histological characteristics, such as mild dysplasia, local invasiveness, and abnormal p53 gene expression, and clinical features, notably a high recurrence rate following excision. [4][5][6][7][8][9] The primary treatment for pterygium is surgical excision. Indeed, over the last two decades, several new approaches in surgical techniques have been proposed and promising success rates have been obtained.…”
Section: Introductionmentioning
confidence: 99%